Occupational stress and personality characteristics: are they related? - I Rosnah,; M.T Azmi, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : To determine association between occupational stress and personality characteristics among nurses at Maternal and Child Health Clinic in the state of Malacca, emphasizing on type of personality and personal perception of stress. Methods : A cross sectional study was conducted among 152 nurses of Maternal and Child Health Clinics in Malacca using self administered questionnaires and selected via multistage sampling. Results : This study showed that a total of 28.3% of the nurses were found to be stressed. Almost half (41.2%) of those who perceived that they were stressed were likely to be really stressed (p = 0.004). Therefore those who perceived themselves to be stressed should be referred for stress evaluation and further management if necessary. However self-perception of stress cannot be used as a screening tool for stress due to its lack of sensitivity (56.8%) and poor Positive Predictive Value (41.2%). Majority of the nurses were of Guardians Personality Type (98%) and 72.4% of them had extrovert trait. However there were no significant associations between stress with personality type or characteristic, most probably due to the preponderance of one personality type or characteristic. Other studied variables such as socio-demographic factors (age, gender, ethnicity, religion, marital status, educational level, body mass index, type of work place, position, duration of service and poverty level) and social factors (placement, chronic medical illness, chronic care taker, smoking status and alcohol drinker) were suggestive of an association between them and stress but were not statistically significant. Conclusion : There is no association between occupational stress and personal characteristics among nurses in Malacca.